Effect of Endometritis on Caesarean Section Scar Thickness: A Sonographic Study - Syed Farooq; Saira Hussain; Shumaim Baila; Maryam Bushra; Saba Majid; Maryam Shahid; Muhammad Tayyab (Jordan Medical Journal, 2025)
Background: Endometritis is an inflammation of the inner lining of the uterus, often caused by infection. It is a common postpartum complication, particularly following a caesarean section (C-section). The thickness of the C-section scar is an important factor in assessing uterine integrity and predicting the risk of complications in subsequent pregnancies. Objective: To examine the effect of endometritis on caesarean section scar thickness in females. Materials & Methods: This was a case-control study conducted at the University Ultrasound clinic, Green town, Lahore for the duration of 7 months. Convenient sampling technique was used to collect the data. The research utilized transabdominal ultrasound scans, employing high-frequency curvilinear transducers of 3.5–6MHz (Toshiba Xario). Results: The mean thickness of the C-section scar was significantly different between the two groups: 2.46 ± 0.54 mm in women without endometritis and 5.29 ± 0.80 mm in those with endometritis (P = 0.000). The number of scars visualized sonographically did not significantly differ between groups. Fluid around the endometrium was significantly more common in the endometritis group (45.3%) compared to none in the no endometritis group (P = 0.000). The number of previous C-sections did not significantly differ between groups (P = 0.580), with similar distributions across both groups. The duration of the C-section procedure was significantly shorter in the endometritis group, averaging 2.79 ± 1.22 minutes compared to 14.5 ± 6.22 minutes in the no endometritis group (P = 0.000). Conclusion: This study demonstrated that endometritis significantly affects the thickness of C-section scars, indicating impaired healing. The presence of fluid around the endometrium and increased endometrium thickness were additional markers of this adverse effect.